2018
DOI: 10.1002/ecs2.2513
|View full text |Cite
|
Sign up to set email alerts
|

Delayed spring onset drives declines in abundance and recruitment in a mountain ungulate

Abstract: Changes in climate are driving widespread landscape changes in northern ecosystems, altering the size and distribution of wildlife populations over multi‐decadal time scales. Extreme weather events are also expected to become more common over time, affecting a variety of species, and mountain ungulates may be particularly susceptible because they occupy habitats with particularly harsh winter weather conditions. To explore the impacts of weather conditions and adverse weather events as population drivers, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 60 publications
(118 reference statements)
3
29
1
Order By: Relevance
“…Bear body size and productivity were generally higher in this subarea as well (Hilderbrand et al 2019 b ), suggesting that greater access to food resources (e.g., large spawning concentrations of chum salmon ( Oncorhynchus keta ) in the lower portions of the Noatak River [Menard et al 2020], beached marine mammals, and a suite of ungulate prey species) may afford a partial explanation. Estimates from the other 3 subareas were similar to those reported for other interior Alaska populations, possibly a function of ≥1 factors, including limited food resources (i.e., limited salmon and lower ungulate densities in the Upper Noatak and Gates of the Arctic; Miller et al 1997, Westing 2012, Rattenbury et al 2018), limited reproductive output in Gates of the Arctic (Hilderbrand et al 2019 a , b ), shorter growing seasons, and higher harvest in the case of the Seward Peninsula.…”
Section: Discussionsupporting
confidence: 66%
“…Bear body size and productivity were generally higher in this subarea as well (Hilderbrand et al 2019 b ), suggesting that greater access to food resources (e.g., large spawning concentrations of chum salmon ( Oncorhynchus keta ) in the lower portions of the Noatak River [Menard et al 2020], beached marine mammals, and a suite of ungulate prey species) may afford a partial explanation. Estimates from the other 3 subareas were similar to those reported for other interior Alaska populations, possibly a function of ≥1 factors, including limited food resources (i.e., limited salmon and lower ungulate densities in the Upper Noatak and Gates of the Arctic; Miller et al 1997, Westing 2012, Rattenbury et al 2018), limited reproductive output in Gates of the Arctic (Hilderbrand et al 2019 a , b ), shorter growing seasons, and higher harvest in the case of the Seward Peninsula.…”
Section: Discussionsupporting
confidence: 66%
“…Recent work has suggested that climate can exert a strong influence on the behavior and demography of Dall’s sheep, but many questions remain. Across Alaska, a decline in recruitment of lambs and survival of adults is strongly affected by spring weather, and the magnitude of the effect varies across latitudes [ 32 34 ]. In the Northern Richardson Mountains of the Yukon in Canada, multiple factors such as potential competition for resources with other herbivores, predation, and emerging diseases could be contributing to observed population declines, however, the effects of documented increases in temperature and precipitation related to climate change remain unknown [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of the effects of weather and climate on wildlife populations includes mortality due to extreme events (e.g., Rattenbury et al 2018), reduction in food resources (e.g., Rutz and Bijlsma 2006;Schmidt et al 2018a, b), and phenological mismatches (Stenseth and Mysterud 2002;Durant et al 2007;Post and Forchhammer 2007). Our findings further suggest that the effects of reductions in resource access can be nuanced and interconnected, thereby playing an important role in determining how variation in weather conditions can influence population dynamics.…”
Section: Discussionmentioning
confidence: 52%
“…Variation in weather and climate influence primary productivity and are important drivers of population dynamics in a variety of vertebrate taxa including ungulates (Post and Stenseth 1999;Rattenbury et al 2018), passerines (Sillett et al 2000;Boelman et al 2017), seabirds (Thompson and Ollason 2001), and raptors (Franklin et al 2000;Fairhurst and Bechard 2005;Glenn et al 2010). The effects of weather and climate can be both direct and indirect, potentially complicating a mechanistic understanding of systems.…”
Section: Introductionmentioning
confidence: 99%